Processing of mesoporous silica materials (MCM-41) from coal fly ash - Misran, H.; Singh, R.; Begum, S.; Yarmo, M.A. (2007)
Mesoporous silica is an important material which has various industrial applications. Currently, it is produced from precursors that are costly. In this paper, the successful preparation of siliceous mesoporous materials MCM-41 with pores of ordered 2-dimensional hexagonal structure by condensation-polymerization using quaternary ammonium salt as structure directing agent and supernatant of the coal fly ash (CIA) as silica precursor is described. The synthesized materials had high surface area of 732 m(2)/g and median pore diameter of 2.5 nm. X-ray diffraction analyses revealed that fusion processes are important in extracting silica from quartz in CFA. SEM images of fused CIA revealed two different morphologies of agglomerated spheres attributable to the fused CFA and distorted octahedral grains to the faujasite phase in comparison to the cenospheres morphology of the as-received CFA. MCM-41 was also produced from pure silica source for comparison. The results obtained in the present work demonstrate the feasibility of employing coal fly ash as a potential source of silica to produce MCM-41 mesoporous materials. (c) 2006 Elsevier B.V. All rights reserved.